2018
DOI: 10.1055/s-0038-1676076
|View full text |Cite
|
Sign up to set email alerts
|

Free Flap Head and Neck Reconstruction with an Emphasis on Postoperative Care

Abstract: Microsurgical free tissue transfer represents the mainstay of care in both ablative locoregional management and the simultaneous reconstruction of a defect. Advances in microsurgical techniques have helped balance the restoration of both form and function—decreasing the significant morbidity once associated with large ablative, traumatic, or congenital defects—while providing immediate reconstruction enabling early aesthetic and functional rehabilitation. There are a multitude of perioperative measures and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 48 publications
0
23
0
2
Order By: Relevance
“…Expert group members completed 2 surveys where draft consensus statements were reviewed and each indicated their agreement according to a 9-point Likert Scale. The scale included the following anchors: (1) strongly disagree, (3) disagree, (5) neutral, (7) agree, (9) strongly agree in response to the request, "Please indicate your agreement with the statement. "…”
Section: Modified Delphi Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Expert group members completed 2 surveys where draft consensus statements were reviewed and each indicated their agreement according to a 9-point Likert Scale. The scale included the following anchors: (1) strongly disagree, (3) disagree, (5) neutral, (7) agree, (9) strongly agree in response to the request, "Please indicate your agreement with the statement. "…”
Section: Modified Delphi Methodsmentioning
confidence: 99%
“…Head and neck cancer patients are often malnourished or unable to feed properly due to the presence of a mass obstructing or compressing the upper aerodigestive tract. [6][7][8][9][10][11] Indexes that describe poor…”
Section: Preoperative Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The best results, in terms of survival, are obtained through a combination of chemotherapy, radiation and surgical treatment. However, surgery on the MFA is often accompanied by complex and serious defects, which can result in disturbance of the functions of chewing, swallowing, respiration, and speech [9][10][11][12][13][14]. Furthermore, cosmetic changes to the face may have a negative infl uence on the patients' mental state, and their return to society is another major problem of MFA and neck tumors.…”
Section: Introductionmentioning
confidence: 99%
“…5,7 Still, they are extremely complex procedures requiring a large swath of resources, and they have the potential to be highly morbid, with either donor or recipient site complications, prolonged intensive care unit (ICU) and hospital stays, and occasionally, mortality. [7][8][9][10][11] As such, it is imperative that these procedures should be performed in an appropriate setting, optimizing outcomes while limiting morbidity. Previous studies have found mostly equivalent outcomes for free flaps performed in university and community hospital settings.…”
mentioning
confidence: 99%